Perlindungan Hukum Bagi Pengasuh Yang Melakukan Tindakan Disiplin Terhadap Taruna Akademi Kepolisian - Amalia Rachim, Zulfa; Sudarmanto, Kukuh; Sofyan, Safran (Journal Juridisch, 2023)
The purpose of this study was to find out the legal basis for the protection of caregivers and the forms of legal protection of caregivers in taking disciplinary action against cadets of the Police Academy and the forms of disciplinary action by caregivers against cadets of the Police Academy who commit disciplinary violations. The police in creating prospective leaders must be specially educated at a Police Education Institution, namely the Police Academy. The Police Academy or often abbreviated as Akpol is an educational institution to produce Polri officers. The Police Academy is an element implementing the education for the formation of Polri Officers who are under Kalemdikpol. In educating police leaders, professional caregivers are needed in educating them. The research method used is normative juridical, namely legal research conducted by examining literature or secondary data as the basis for research by conducting a search of regulations and literature related to the problem under study. The results of this study indicate that the legal basis for the protection of caregivers in carrying out disciplinary actions against Police Academy Cadets is the 1945 Constitution, Law No. 23 of 2003 concerning the National Education System, Law No. 14 of 2005 concerning Teachers and Lecturers, Government Regulation No. 74 of 2008 Concerning Teachers, PGRI MoU with POLRI No B/53/XII/2012 and 1003/UM/PB/XX/2012 Concerning the Protection of the Teacher Profession, Supreme Court Decision No 1554 K/Pid/2013 Concerning Reasons for Penalizing Teachers Who Commit Disciplinary Actions , Regulation of the Head of the Police Education and Training Institute No. 1 of 2021 Concerning the Life of Students at the Police Academy, Regulation of the Head of the Police Education and Training Institute No. 3 of 2021 concerning Assessment of Educational Outcomes of Police Academy Cadets, Regulation of the Head of the Police Education and Training Institute No. 2 of 2021 Concerning the Academy Council at the Police Academy, reasons for abolishing crimes that are outside the law (KUHP). The form of legal protection for caregivers in carrying out disciplinary actions against Police Academy Cadets is that there are reasons for eliminating crimes that are outside the law (KUHP), namely the rights of parents and teachers to discipline their children or students (tuchtrecht). Thus caregivers who take disciplinary action against Police Academy cadets cannot be punished. Forms of disciplinary action by caregivers against Police Academy Cadets who commit disciplinary violations, namely direct reprimand, giving special educational assignments, other physical actions that are coaching in nature. In taking action against the offenders, the role of Urgakplin (Disciplinary Enforcement Affairs) is needed because URGAPLIN is an element of discipline for cadets as well as security and cleanliness of flats, including violations of Perkalemdikpol, as an element of prosecution for violations committed by cadets, carrying out analysis and evaluation of cadets who commit violations .